Pengembangan Book Creator Sebagai Media Pembelajaran Maharah Qira’ah Pada Tingkat Universitas - Hidayat, Indra Syarif; Aminudin; Maksum, M. Syukron; Fitri, Yeni Nuriah (AL-MUTSLA, 2025)
This study aims to develop and test the feasibility of Book Creator-based digital learning media in improving students' reading skills (Maharah Qira'ah) at the university level. The background of this study is based on the low level of media innovation in Arabic language learning, which is still conventional and textbook-centered, resulting in students being less motivated and quickly feeling bored. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were postgraduate students of UIN Maulana Malik Ibrahim Malang. The results of the validation test showed that the Book Creator media obtained a validity score of 66.7% with the category of "quite valid", while the practicality test obtained an average score of 66.7% with the category of "quite practical". These findings indicate that Book Creator is suitable for use as an alternative digital-based learning media in the Maharah Qira'ah course, because it is able to combine text, images, and audio interactively to increase student engagement and motivation to learn. However, further improvements are needed in the aspects of visual design, audio quality, and learning evaluation to make the media more effective and comprehensive